Bacterial Communities in Acid Tea Soils Treated for 10 Years with Chemical vs. Integrated Fertilizers. Issue 3 (4th February 2019) - Wang, Limin; Huang, Dongfeng; Wang, Fei; Li, Qinghua; He, Chunmei; Liu, Cailing; Huang, Yibin
ABSTRACT: MiSeq sequencing approach was used to estimate bacterial community structure and diversity in acid tea ( Camellia sinensis (L.) Kuntze) soils treated with 10 yr of non-fertilization control (CK), chemical fertilizers only (CF), and the integrated use of chicken manure and legume straw with chemical fertilizers (IF), respectively. We found that the most predominant phyla in acid tea soils are Proteobacteria, Chloroflexi, and Acidobacteria . Moreover, IF resulted in the prevalence of the genera Bradyrhizobium, Haliangium, Nitrospira, Roseiflexus, Ramlibacter, and Flavobacterium, which accounted for 2.02%, 1.56%, 2.33%, 2.22%, 1.07%, and 1.03% of the total bacteria, respectively. Additionally, the relative abundances of the phyla Nitrospirae, Latescibacteria, Fibrobacteres, and Microgenomates were positively correlated with pH, total N (TN), soil organic carbon (SOC) and soil moisture (SM) contents. Together, these results suggest that the integrated fertilizer regimes may affect pH, SM, TN, and SOC contents, which in turn influence soil bacterial community structure.